Validation of the acenocoumarol EU-PACT algorithms: similar performance in the Rotterdam Study cohort as in the original study - van Schie, Rianne MF; el Khedr, Nadia; Verhoef, Talitha I; Teichert, Martina; Stricker, Bruno H; Hofman, Albert; Buhre, Peter N; Wessels, Judith AM; Schalekamp, Tom; le Cessie, Saskia; van der Meer, Felix JM; Rosendaal, Frits R; et al. (Pharmacogenomics, 2012)
To evaluate the performance of the European Pharmacogenetics of Anticoagulant Therapy (EU-PACT) acenocoumarol dose algorithms in an independent data set. The EU-PACT trial investigates the added value of pretreatment genotyping for use of warfarin, phenprocoumon and acenocoumarol. External validation was performed in the Rotterdam Study cohort using information about 707 acenocoumarol users. R , which measures the strength of correlation between the predicted and observed acenocoumarol dose, mean absolute error and mean squared error were calculated to evaluate the performance of the original algorithm. Validation resulted in a R of 52.7 and 12.9% compared with an R of 52.6 and 17.8% in the original study for the genotype-guided and nongenotype-guided dose algorithm, respectively. For the genotype-guided dose algorithm, the mean absolute error was 0.48 mg/day and the mean squared error was 0.38 (mg/day) . For the nongenotype-guided dose algorithm, the mean absolute error was 0.62 mg/day and the mean squared error was 0.63 (mg/day) . The EU-PACT acenocoumarol algorithm performs just as accurately in this study as in the original study, which implies applicability in various populations. Original submitted 4 April 2012; Revision submitted 31 May 2012